Lack of phenotypic additive effect of familial defective apolipoprotein B3531 in familial hypercholesterolaemia. Issue 4 (22nd April 2021) - Giammanco, Antonina; Spina, Rossella; Fayer, Francesca; Barbagallo, Carlo M.; Noto, Davide; Cefalù, Angelo B.; Averna, Maurizio R.
Abstract: Familial defective apolipoprotein (apo) B (FDB) and familial hypercholesterolaemia (FH) are the two common genetic conditions that cause hypercholesterolaemia. R3531C mutation of the APOB gene is a rare cause of FDB. Individuals with both FDB and FH are rare. A 51‐year‐old man with hypercholesterolaemia (11.4 mmol/L) and his family were studied. Low‐density lipoprotein (LDL) receptor ( LDLR ) and APOB genes were analysed by direct sequencing. LDL of four subjects were studied in a fibroblast LDL receptor‐binding displacement assay. We found a mutation of the LDLR gene (p.Y398X) in the proband and in four other family members: the p.R3531C APOB gene mutation was also found in the proband, his father and his children. The proband and his son were thus compound heterozygotes for both FH and FDB. Double heterozygotes did not show higher cholesterol levels compared to carriers of LDLR gene mutation alone. LDL from one of the carriers of the p.R3531C alone exhibited a binding ability, which was similar to a normal subject. This is the first report in Italy of the p.R3531C mutation, and our results show that this mutation has no effect in LDLR p.Y398X/ APOB p.R3531C double heterozygotes.